Rapid Sintering and Synthesis of a Nanocrystalline Fe-Si3N4 Composites by High-Frequency Induction Heating - Ko, In-Yong; Du, Song-Lee; Doh, Jung-Mann; Yoon, Jin-Kook; Park, Sang-Whan; Shon, In-Jin (KOREAN INST METALS MATERIALS, 2011)
Nanopowders of Fe3N and Si were fabricated by high-energy ball milling. A dense nanostructured 12Fe-Si3N4 composite was simultaneously synthesized and consolidated using a high-frequency induction-heated sintering method for 2 minutes or less from mechanically activated powders of Fe3N and Si. Highly dense 12Fe-Si3N4 with a relative density of up to 99% was produced under simultaneous application of 80 MPa pressure and the induced current. The microstructure and mechanical properties of the composite were investigated.
Keywords: MECHANICAL-PROPERTIES; TEMPERATURE